The ultimate study skills handbook - Moore, Sarah (Open UP study skills, 2010)
Covering all the core skills you will need to help you make the most of your university course, 'The Ultimate Study Skills Handbook' is your key to success. It provides the techniques, tips and exercises that will help improve your grades, save you time and hone the skills that will make you stand out to prospective employers